The TSC-2 product tuberin is expressed in lymphangioleiomyomatosis and angiomyolipoma - Johnson, S R; Clelland, C A; Ronan, J; Tattersfield, A E; Knox, A J (Histopathology, 2002)
The TSC‐2 product tuberin is expressed in lymphangioleiomyomatosis and angiomyolipoma Aims: Lymphangioleiomyomatosis is categorized by proliferation of abnormal smooth muscle cells (LAM cells) in the lungs and lymphatics and the presence of angiomyolipomas. Recently mutations in the tuberous sclerosis complex‐2 gene (TSC‐2) have been described in LAM cells and angiomyolipomas. The TSC‐2 protein tuberin is a tumour suppressor and its loss may result in cellular proliferation. We used immunohistochemistry to test the hypothesis that uncontrolled cellular proliferation in lymphangioleiomyomatosis is the result of reduced tuberin protein expression. Methods and results: Tissue from normal lung, normal kidney, lymphangioleiomyomatosis and angiomyolipomas was immunostained with three separate anti‐tuberin antibodies. Tuberin staining in normal tissues was similar to that previously described. Surprisingly, tuberin was strongly expressed in the LAM cells of all cases of lymphangioleiomyomatosis and angiomyolipoma at a greater level than in normal smooth muscle cells. The perivascular cells of angiomyolipomas, however, did not stain for tuberin. Conclusions: Our results suggest that a loss of tuberin protein in LAM cells is not the cause of the cellular proliferation seen in lymphangioleiomyomatosis. Lymphangioleiomyomatosis may result either from the expression of a mutant tuberin with abnormal function, as a result of mutations in functionally related proteins, or from more than one mechanism.